PELAKSANAAN PEMBINAAN KEMANDIRIAN BAGI NARAPIDANA DI LAPAS PEREMPUAN KELAS IIA JAKARTA (PERIODE 1 MEI SAMPAI 31 JULI 2024) - Amaliah, Fitri; Anita Sinaga, Niru (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The correctional system is organized for the purpose of improving the quality of personality and independence of inmates. One of the correctional systems is personality development carried out at the Class IIA Jakarta Women's Prison. The problem regarding personality development is an inhibiting factor in the implementation of independence development for inmates at the Class IIA Jakarta Women's Prison. What is the solution to the implementation of independence development for inmates at the Class IIA Jakarta Women's Prison? The purpose of this study was to determine the solution to the implementation of independence development for inmates at the Class IIA Jakarta Women's Prison. This research method uses normative research, namely research conducted by analyzing written laws from library materials or secondary data. The implementation of independence development for inmates at the Class IIA Jakarta Women's Prison (Period 1 May to 31 July 2024) is to organize a socialization campaign to educate the public about the importance of rehabilitation and reintegration of inmates. Finally, by streamlining administrative procedures by eliminating unnecessary steps and accelerating the licensing and approval process and implementing a digital administration system to reduce overlapping work and accelerate data and document processing. Inhibiting factors in the implementation of independence coaching for inmates at Class IIA Jakarta Women's Prison are from officers and experts in the prison. Then there are factors from inmates, community factors, facilities and infrastructure factors and administrative factors. To overcome these obstacles, it is done by sending officers to attend technical correctional and administrative training, and holding motivational programs, such as seminars, workshops, and counseling sessions aimed at increasing the spirit and motivation of inmates.